NEGATIV-ADJEKTIVBILDENDE AFFIGIERUNG IM MAGAZIN DER SPIEGEL: EINE MORPHO-SEMANTISCHE ANALYSE - Lafradi Zenobia Farisi Pagih, - (2022)
Morphology is the study of the internal structure of words. One of the subjects covered in morphology is affixation. In German grammar and morphology, affixation is the process of adding a morpheme-or affix-to a word to create either a different form of that word or a new word with a different meaning. This study entitled Negative Adjectives Affixation in DER SPIEGEL Magazine is a morpho-semantic that aims to investigate affixes in the DER SPIEGEL Magazine, morphologically analyze negative affixation process in adjectives, and semantically classify said adjectives. Using a descriptive qualitative approach as a research method, this study employs the theoretical framework proposed by Bünting (1996) to investigate words structure and Duden (2009) to semantically classify adjectives found in the data. The data used in this study are taken from DER SPIEGEL Magazine and it is limited to identification of negative adjectives, analysis of how said negative adjectives are formed, and classification of adjectives according to its semantic features. Based on the data, it is found that 1) there are appearances of un-, in-/il-/ir-, a-, des-/dis- as prefixes and -los as suffix, 2) In German, the affixation process of negation to adjective do not change the meaning of the base words, therefore the affixes add only grammatical change. It appears that change of meaning through negative affixation applies to only a small number of word class, 3) negation found in affixed adjectives are semantically classified into four categories: participle adjective, qualitative adjective, relational adjective, and numeral adjective. Keywords: adjective, affixation, morpho-semantic, negation Morphologie ist ein Teilgebiet der Linguistik, die sich mit der Wortbildung umfasst. Eine der Forschungsstudien der morphologischen Analyse ist die Affigierung. Unter Affigierung versteht man die Anfügung eines gebundenen Morphems an ein freies Morphem, das den lexikalischen Inhalt des Morphems verändern kann. Im Deutschen kann die Negation durch die Anfügung des Affixes an Verben, Substantive und Adjektive angehängt werden. Diese Untersuchung mit dem Titel Negativ-adjektivbildende Affigierung im Magazin DER SPIEGEL ist eine morpho-semantische Analyse, deren Zweck ist, die negativen Affixe zu finden, den morphologischen Prozess bei der Wortbildung zu analysieren und zuletzt die negativen Adjektive nach der semantischen Klassifizierung einzuordnen. Diese Untersuchung ist eine qualitative Untersuchung und erfasst die Ableitungsmuster der Wortbildung anhand der Theorie von Bünting (1996) und die semantische Klassifizierung der Adjektive laut Duden (2009) zur Analyse. Die in dieser Untersuchung verwendeten Daten wurden vom Magazin DER SPIEGEL gesammelt. Die Verfahren der Datenerhebung sind wie folgt: Identifizierung der angehängten negativen Adjektive, Analyse der Wortbildung, Klassifizierung der Adjektive semantisch und zuletzt die Zusammenfassung bzw. das Ziehen der Schlussfolgerung aus den gesammelten und analysierten Daten. Aus der Analyse stellt sich heraus, dass (1) es das Präfix un- in-/il-/ir- a-, des-/dis- und das Suffix -los gibt, die Adjektive verneinen können; (2) es bei der Ableitung die lexikalische Bedeutung des Stammworts am häufigsten unverändert bleibt; (3) die Adjektive, an die negative Affixe angehängt werden, semantisch in vier Kategorien einzuteilen sind: adjektivisch Partizipien, qualifizierende Adjektive, relationale Adjektive und Zahladjektive. Schlüsselwörter: Adjektive, Affigierung, Morpho-semantik, Negation